Community Organising against Racism : 'Race', Ethnicity and Community Development - Craig, Gary, 1944- (Book collections on Project MUSE., 2018)
Gary Craig and his contributors blend theory and practice-based case studies to review how different community development approaches can empower minority ethnic communities to confront racism and overcome social, economic and political disadvantage.